How does understanding stress response mechanisms in inhabitants help us build a resilient city? - Mierzejewska, Lidia; Śliwowska, Joanna H.; Lechowska, Ewa; Wdowicka, Magdalena; Szejnfeld, Marta; Modrzewski, Bogusz; Sikorska-Podyma, Kamila; Hoffmann-Pawlak, Natalia; Grzęda, Emilia (Quaestiones Geographicae, 2025)
Long-lasting (chronic) stress leads to many adverse effects in living organisms. In this study, the city is perceived as an organism. Thus, the recognition of physiological mechanisms of stress response and coping with it in an organism will help identify and develop similar defence mechanisms in urban organisms. This study proposes a multidisciplinary approach and is aimed at applying the stress response mechanisms of living organisms to cities in order to build stress resilience in case of threat. The long-term impact assessment effects of the COVID-19 pandemic and the restrictions and lockdowns introduced are of particular interest. In the review, we present a theoretical, multidisciplinary approach to building a stress-resilient city suitable for academics and a global audience, and propose concrete strategies for city policymakers to cope with stressors at the level of its inhabitants as well as regulations and management. Mitigation, re-construction, and new urban governance have been recognised as such strategies and likened to shortand long-term stress responses of living organisms. Thus, we have offered policymakers a solution for building a resilient city. A novel model of environmental governance, propositions of intervention, and recommendations have been created that could be used by local city authorities to rebuild citizens’ resilience in post-pandemic times.